Aplicação da técnica de test-driven design para a avaliação de algoritmos de modulação em conversores conectados à rede - Guterres, Tiarles da Rocha Moralles (2021)
The thesis presents an approach to evaluate techniques in Grid-Tied Converters using Test-Driven Design (TDD). It is done a review of the existent semiconductors in the market to produce and manufacture Voltage Source Inverter (VSI) in its electronic and losses aspects. Also, is proposed a series of metrics from standards to certify Grid- Tied Converters, and a model to obtain the switching losses characteristic curve of these semiconductors. To cover a significant amount of configurations the TDD was applied to develop, verify and validate modulation strategies for two and three-level converters. With TDD is possible to automate Hardware-In-the-Loop (HIL) tests using the Python language, the pytest framework, and the TyphoonTest IDE tool to interface the schematics and the tests developed to evaluate the simulation scenarios setup. The introduction of TDD brought a new way to approach projects in power electronics, abling the insertion of many simulation scenarios in an automatic shape with a self-documented report that makes easier the analysis of all test results, and allowing the developers a bigger design coverage to be deployed in the market.